Transpersonale onderwys van die New Agebeweging: 'n evaluering en perspektiefstelling - Steyn, Jeannette (Koers, 1993)
After analysing Transpersonal Education as a view espoused by the New Age, the conclusions reached were that * Transpersonal Education is a spiritual event, an experience of a new awareness characterised by the incarnation of the sacred; further, * the teacher should bring about this awareness in the child by spiritual transformation through karma, darma and rituals such as yoga and meditation. According to this school of thought self-actualization stimulates the power in oneself and unleashes dark forces deep inside the soul. This point of view implies human autonomy and the power to govern human affairs by the human spirit. It is therefore an inevitable conclusion that Transpersonal Education as the view of the New Age accentuates the spiritual character of man and therefore minimizes the other functions of man, so that Transpersonal Education can not be regarded as anything other than educationally unbalanced and ScripturaUy unsound.